2017
DOI: 10.1242/dev.150110
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal LRP4 regulates synapse formation in the developing CNS

Abstract: The low-density lipoprotein receptor-related protein 4 (LRP4) is essential in muscle fibers for the establishment of the neuromuscular junction. Here, we show that LRP4 is also expressed by embryonic cortical and hippocampal neurons, and that downregulation of LRP4 in these neurons causes a reduction in density of synapses and number of primary dendrites. Accordingly, overexpression of LRP4 in cultured neurons had the opposite effect inducing more but shorter primary dendrites with an increased number of spine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 40 publications
3
43
0
Order By: Relevance
“…Lrp4, like Agrin and MuSK, is expressed in the CNS. Although the roles for Agrin and MuSK in the CNS are not well understood, several studies have demonstrated that Lrp4 has an important role in the development of CNS synapses [ 72 , 73 , 74 , 75 ]. How Lrp4 functions to control CNS development is not understood.…”
Section: Fundamental Proteins Of the Neuromuscular Synapsementioning
confidence: 99%
“…Lrp4, like Agrin and MuSK, is expressed in the CNS. Although the roles for Agrin and MuSK in the CNS are not well understood, several studies have demonstrated that Lrp4 has an important role in the development of CNS synapses [ 72 , 73 , 74 , 75 ]. How Lrp4 functions to control CNS development is not understood.…”
Section: Fundamental Proteins Of the Neuromuscular Synapsementioning
confidence: 99%
“…Knockdown of LRP4 in embryonic cortical and hippocampal neurons causes a reduction in density of primary dendrites, overexpression of LRP4 in these cultured neurons had the opposite effect inducing more but shorter primary dendrites (Karakatsani et al, 2017). Neuron-specific knockdown of LRP4 by in utero electroporation of LRP4 miRNA also resulted in neurons with fewer primary dendrites in the developing cortex and hippocampus in vivo (Karakatsani et al, 2017). Embryonic cortical neurons from Lrp4 mitt mice had fewer but longer primary dendrites and transfection of agrin compensated the dendritic branching deficits in LRP4-deficient neurons (Handara et al, 2019).…”
Section: Discussionmentioning
confidence: 92%
“…LRP4 plays a crucial role in CNS, including maintaining synapses, especially in synaptic transmission [18,19]. Studies demonstrated that in the brain glutamate release was reduced in lacking LRP4 mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the cells grow in a flattened manner, there is not much information lost in the z -axis if the purpose is to score for a marker expressed all over the cell. However, if one wishes to adapt this protocol to study sub-cellular features such as dendritic morphogenesis or synaptogenesis, 6 , 7 these are best assessed in confocal images that provide the resolution needed for detailed sub-cellular or structural analysis.…”
Section: Anticipated Resultsmentioning
confidence: 99%